Evaluation of astrocytoma cell proliferation using diffusion-weighted imaging: correlation with expression of proliferating cell nuclear antigen - Zhang Kai; Li Chuanfu; Liu Ying; Li Li; Meng Xiangshui; Feng Dechao; Ma Xiangxing (Translational Neuroscience, 2015)
The purpose of this study was to analyze if there is a significant correlation between the results of diffusionweighted imaging (DWI) and the expression of proliferating cell nuclear antigen (PCNA) in astrocytomas. The DWI scans of 19 different-grade astrocytomas were obtained on a 3 T magnetic resonance scanner. The average regional apparent diffusion coefficients (ADC) were measured. The positive expression of PCNA was determined immunohistochemically by using streptavidin-peroxidase complex staining, and was quantified by calculating its calibrated opacity density (COD) using an image analysis system. The average regional ADC and PCNA COD of low grade and high grade astrocytomas were compared. Correlations between regional ADC and PCNA COD were analyzed. The average regional ADC of high grade astrocytomas was significantly (t = 10.169, P = 0.000) less (0.687 ± 0.225 x 10-3 mm2/s) than that of low grade astrocytomas (1.572 ± 0.333 x 10-3 mm2/s). The PCNA COD (0.343 ± 0.052) of high grade astrocytomas was significantly (t=-7.858, P=0.000) greater than that (0.194 ± 0.012) of low grade astrocytomas. There were strong negative correlations between regional ADC and PCNA COD (r = -0.801, P = 0.000). The results demonstrated that DWI is helpful in evaluating cell proliferation and preoperatively grading astrocytomas by measuring regional ADC.